2017
DOI: 10.2174/1567205014666170117094757
|View full text |Cite
|
Sign up to set email alerts
|

A Multicentre Italian Validation Study in Aging Adults with Down Syndrome and Other Forms of Intellectual Disabilities: Dementia Screening Questionnaire for Individuals with Intellectual Disabilities

Abstract: The present study confirms the cross-cultural value of DSQIID which was proved to be a psychometrically valid and user-friendly observer-rated scale for dementia screening in adults with both DS and non-DS ID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…[47] reported the sensitivity of the DLD as 0.65 and specificity 0.93. The instrument was found to be a good marker of the cognitive and affective symptoms observed in the early signs of dementia [65], and displays good inter-test validity with other instruments like the SIB [53] and the Alzheimer's…”
Section: Cross-sectional Studies In Participants With Down Syndromementioning
confidence: 89%
See 1 more Smart Citation
“…[47] reported the sensitivity of the DLD as 0.65 and specificity 0.93. The instrument was found to be a good marker of the cognitive and affective symptoms observed in the early signs of dementia [65], and displays good inter-test validity with other instruments like the SIB [53] and the Alzheimer's…”
Section: Cross-sectional Studies In Participants With Down Syndromementioning
confidence: 89%
“…Cross-Sectional Studies Including Participants with DS and other IDThe DLD[38,39,40] revealed good psychometric properties in studies with participants with both DS as other ID. Eight studies used the DLD[47,61,62,63,64,65,66,67] Shultz et al (2004).…”
mentioning
confidence: 99%
“…Our study has several strengths. First, the 15 structures and organizations, managed by different stakeholders, parental associations, public health services, cooperatives or local institutions can be considered representative of the Italian scenario offering services to more than 3,000 adults and elderly with ID both in small rural areas and in medium and large urban areas, distributed over most of the national territory ([ 22 ] see Fig. 1, p. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Medication data for this study was drawn from a multicenter Italian validation study of the Dementia Screening Questionnaire in Intellectual Disabilities (DSQIID) which has been described in detail elsewhere [ 21 , 22 ]. In summary, 15 organizations and structures each one with previous experience in DMR-I screening [ 23 ] enrolled 398 subjects with ID aged 40 years and over.…”
Section: Methodsmentioning
confidence: 99%
“…(2) history of symptoms of dementia from family members and/or caregivers; (3) medication status; (4) screening for dementia symptoms using the DSQIID (Deb et al, 2007), which has been shown to be a valid and reliable observer-rated questionnaire for screening for dementia among adults with DS and has also been validated by an Italian group (Gomiero et al, 2017); (5) physical and neurological examinations; (6) psychiatric assessment of symptoms of depression; (7) (Aylward et al, 1997). After completion of the diagnostic workup, a multidisciplinary staff established a consensus diagnostic classification.…”
Section: Clinical Assessmentmentioning
confidence: 99%